The Effect of the Non-task Language When Trilingual People Use Two Languages in a Language Switching Experiment - Chen, Jianlin; Liu, Hong (Frontiers in Psychology, 2020)
This study investigated the effect of non-task language in language switching experiment. Non-task language refers to participants’ language(s) (regardless of proficiency level) that are not used in any trials throughout the experiment. We recruited 60 Tibetan-Chinese-English trilinguals (grade-12 high school students with a median age of 17) to perform a lexical decision (word vs. non-word) task in only two of their languages. We repeated the experiment three times to present each language pair once. In each experiment, the participants were divided into two groups which significantly contrasted with each other in their non-task language while remained comparable in the two task languages. Response time (RT) and error rate (ER) have been examined to evaluate task performance. The interaction between task performance and the participants’ proficiency in the non-task language was also examined. The results showed null effect of language switching. In addition, the effect of the non-task language was not found. These results were interpreted with reference to the main models of bilingual visual word recognition and the role of orthography specificity.